2015
DOI: 10.1128/jcm.01149-15
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Solid Medium for Culturing Mycobacterium tuberculosis Isolates from Clinical Specimens

Abstract: The laboratory diagnosis of tuberculosis usually relies on culture-based isolation of the causative Mycobacterium tuberculosis bacteria. We developed and evaluated the performance of MOD9, a new blood-free derivative of the MOD4 solid medium on which we previously reported for the isolation and culture of mycobacteria. First, inoculation of Lowenstein-Jensen medium with 21 M. tuberculosis isolates at 10 5 , 10 3 , and 10 CFU yielded colonies in 5.7 ؎ 1.5 days, 7.6 ؎ 0.8 days, and 10.8 ؎ 1.7 days versus 1.5 ؎ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
(14 reference statements)
0
20
0
1
Order By: Relevance
“…However, contamination is a major limitation of culturing feces. Here, we applied to animal feces a 1% chlorhexidine decontamination and MOD9 medium culture protocol suitable for the recovery of Mycobacterium tuberculosis complex in patients on diagnosed with pulmonary tuberculosis 29,30 . Because the level of contamination of swine feces is very high, an efficient decontamination protocol is essential to isolate and culture mycobacteria from this type of sample 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contamination is a major limitation of culturing feces. Here, we applied to animal feces a 1% chlorhexidine decontamination and MOD9 medium culture protocol suitable for the recovery of Mycobacterium tuberculosis complex in patients on diagnosed with pulmonary tuberculosis 29,30 . Because the level of contamination of swine feces is very high, an efficient decontamination protocol is essential to isolate and culture mycobacteria from this type of sample 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The MOD9 culture medium was prepared as previously described 29,30 . Briefly, MOD 9 culture medium incorporates for a total volume of 1.000 mL, 5 g of lecithin, 19 g of Middlebrook 7H10 powder, one gram of yeast extract, two grams of glucose, one gram of pancreatic digest of casein, 5 mL of glycerol and 2 mL of Tween 80.…”
Section: Methodsmentioning
confidence: 99%
“…40 Drug susceptibility testing on solid or liquid culture is essential to confirm a diagnosis of MDR-TB, but its availability in low-income and high-burden areas is far less than is needed. Molecular tests, such as GenoType MTBDRplus, a line probe assay, that rapidly detects TB bacteria and identifies resistances to the most important first-line drugs (rifampicin and isoniazid) and to some second-line molecules in its latest version, are often used as substitutes for conventional drug susceptibility testing, although their implementation is still challenged by high costs and complex technical requirements.…”
Section: Tb Diagnostics: Past Present and Futurementioning
confidence: 99%
“…Comparison of MOD9 with LJ (chlorhexidine-0.7% decontamination) showed that MOD9 had a higher sensitivity, shorter time to detection of M. tuberculosis and lower contamination rate (95%, 10.5 ± 4.2 days and 1.6%) than LJ (80%, 18.1 ± 6.3 days and 4.4%; Asmar et al, submitted). Furthermore, the comparison of MOD9 medium (chlorhexidine-0.7% decontamination) with Bactec 960 MGIT (NALC–NaOH decontamination) showed that MOD9-chlorhexidine-0.7% had a higher sensitivity, shorter time to detection and a lower contamination rate (95.8%, 10.1 ± 3.9 days and 1.7%, respectively) than Bactec MGIT 960–NALC–NaOH (40.8%, 14.7 ± 7.3 days and 5.7%; Asmar et al, 2015 ). Combining MOD9 with scanning technology (Advencis-Bio-system) enabled the detection of M. tuberculosis colonies in 3.4 ± 2 days vs. 15 ± 6 for Bactec MGIT 960 (Ghodbane et al, 2014 , 2015 ; Table 1 ).…”
Section: Introductionmentioning
confidence: 99%